First record of Praetorblissus from Mexico (Hemiptera: Heteroptera: Lygaeoidea: Blissidae), with the description of a new species associated with bamboo - Peredo, Luis Cervantes; Brailovsky, Harry (Zootaxa, 2013)
Praetorblissus mexicanus is described as a new species of Blissidae. This species represents the first record of the genus for Mexico and expands its northern limit of distribution. The species was collected in a pine area in the state of Oaxaca associated with the bamboo Chusquea repens. A key is included to separate all the species in the genus.